Upaya Pencegahan Tindakan Plagiarisme untuk Meningkatkan Kualitas Penulisan Karya Tulis Ilmiah di Dalam Pembimbingan Tugas Akhir (Skripsi) Bagi Mahasiswa STIE Jambi - Laila Farhat (Universitas Batanghari, 2019)
This study aims to describe plagiarism in writing final assignments for students at STIE Jambi. This research was conducted at the Management Study Program at STIE Jambi. Data were collected through interviews and in-depth observations, and analyzed using explanatory approaches, specifically qualitative descriptive techniques. The findings obtained indicate that plagiarism in thesis writing includes duplication, which consists of (1) duplication of titles, (2) duplicate themes, (3) duplication of theories, (4) duplication of data, and (5) duplication of references. The process approach in writing this thesis can be used to prevent plagiarism. Such an approach consists of the following steps: return the draft thesis, show the original source, and cancel the thesis. This can be done by investigating, discussing, evaluating, and presenting the title and substance of the thesis. And the final results of finalizing the thesis are done by doing book printing, the printing of this book is intended as a reference material, input and knowledge / teaching material for the next student in scientific writing / thesis writing techniques to avoid plagiarism and increasing interest in writing scientific papers .